2021
DOI: 10.34172/aim.2021.34
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Pathology of Acute Lymphoblastic Leukemia in Iran with Evaluation of Incidence Trends of This Disease Using Joinpoint Regression Analysis

Abstract: Background:The aim of present study is to determine the spatial-temporal epidemiology of acute lymphoblastic leukemia (ALL) in Iranian children. Methods: This ecological study was performed using an exploratory mixed design. The study population consists of 3769 children with ALL who were reported in the National Cancer Registry Program of Iran from 2006 to 2014. Data analysis was conducted using Mann-Whitney U, joinpoint regression analysis, Global Moran's I and Anselin Local Moran's I. Results: The average a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The p-value was calculated using the Monte Carlo method and with 4499 repetitions. Also, Bayesian information criterion (BIC) and Sum of Squared Errors (SEE) were considered to evaluate the precision of the models and select the best model [ 19 ]. To identify the exact time of joins, Average Annual Percent Change-Annual Percentage Change (AAPC-APC) values and slop changes in the estimated regression line with 95% confidence interval for the annual disease course during 2015–2020 were obtained by type of diabetes.…”
Section: Methodsmentioning
confidence: 99%
“…The p-value was calculated using the Monte Carlo method and with 4499 repetitions. Also, Bayesian information criterion (BIC) and Sum of Squared Errors (SEE) were considered to evaluate the precision of the models and select the best model [ 19 ]. To identify the exact time of joins, Average Annual Percent Change-Annual Percentage Change (AAPC-APC) values and slop changes in the estimated regression line with 95% confidence interval for the annual disease course during 2015–2020 were obtained by type of diabetes.…”
Section: Methodsmentioning
confidence: 99%
“…The closer the value of the statistic is to +1, the more it is clustered, and the closer it is to -1, the more it is dispersed, Furthermore, if its value is zero, the spatial distribution of the phenomenon is random. The null hypothesis indicated that the distribution of drug poisoning was randomly dispersed in Semnan Province (13,16). The Kuldorff's purely spatial scan statistic test and the Gini Optimized Cluster Collection method were used to detect the high-risk and low-risk clusters and estimate the relative risk of drug poisoning in any county of Semnan Province.…”
Section: Methodsmentioning
confidence: 99%
“…The Kuldorff's purely spatial scan statistic test and the Gini Optimized Cluster Collection method were used to detect the high-risk and low-risk clusters and estimate the relative risk of drug poisoning in any county of Semnan Province. This new method separates clusters on a more local scale and optimizes the radius of the circular scanning window for cluster detection, thereby demonstrating the best results in cluster detection (13,16,17).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Disease monitoring provides the basis for conducting research programs on the cause of the disease and evaluating early public health interventions (6). The incidence, prevalence, and deaths of diseases change over time (10). Temporal statistics are used to identify time trends.…”
Section: Introductionmentioning
confidence: 99%